Doppler Ultrasonographic Evaluation of Maternal and Foetal Blood Flow in Bitches Approaching Delivery by Different Whelping Modes - Devarajan, Nayana; Simon, Shibu; Jayakumar, Choppillil; Aravind, Amritha; B, Sunil; Mani, Binu K (The Indian Journal of Animal Reproduction, 2025)
Present study included 28 healthy bitches which, based on modes of whelping, were divided into four groups viz., Group I (Vaginal whelping/VW), Group II (elective caesarean section/CS), Group III (emergency CS) and Group IV (induction of whelping). Doppler evaluations were conducted within one hour before whelping to assess blood flow measurements in the uteroplacental artery (UPA), umbilical artery (UMA), and fetal abdominal aorta (FAA) using pulsatility (PI) and resistance indices (RI). The mean PI and RI of UPA were 1.10 ± 0.06, 1.30 ± 0.09, 1.07 ± 0.06, and 1.07 ± 0.10, and 0.62 ± 0.02, 0.71 ± 0.02, 0.64 ± 0.02 and 0.66 ± 0.04 respectively, in Groups I, II, III and IV. The mean PI and RI of UMA were 1.26 ± 0.05, 1.39 ± 0.07, 1.23 ± 0.07 and 1.21± 0.11, and 0.67 ± 0.01, 0.73 ± 0.02, 0.70 ± 0.03 and 0.67 ± 0.03 respectively, in the aforesaid groups. The mean PI and RI of FAA were 1.36 ± 0.11, 1.55 ± 0.10, 1.55 ± 0.07 and 1.40 ± 0.16, and 0.73 ± 0.02, 0.72 ± 0.02, 0.75 ± 0.01 and 0.71 ± 0.03, respectively in the aforesaid groups. No significant difference (p>0.05) could be noticed in the mean PI and RI of different vessels between the groups on the day of parturition. Increased Doppler indices, especially in the UPA, close to whelping may result from reduced diastolic blood flow to the uterus due to uterine contractions.
Keywords: Doppler ultrasonography; Pulsatility index; Resistance index